2019
DOI: 10.12659/msm.912863
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Smoking and Passive Smoking with Multiple Sclerosis and the Underlying Molecular Mechanisms

Abstract: Multiple sclerosis (MS) is a chronic immune-mediated disease of the spinal cord and brain. Many studies have shown that smoking and passive smoking are key environmental risk factors for MS.Here, we provide an overview of the human leukocyte antigen (HLA) gene studies on smoking and MS risk, and we discuss recent studies on between epigenetics and smoking-induced MS. In addition, in this review we also summarize current research advances in biological pathways and smoking-induced MS.This review provides an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 102 publications
(104 reference statements)
0
12
0
6
Order By: Relevance
“…It is also suggested that nutritional interventions may provide a better outcome for patients diagnosed with dementia ( Chen et al , 2019 ). Furthermore, the evidence for the direct and possible indirect association between tobacco and Alzheimer’s disease, as well as tobacco and multiple sclerosis, is presented in previous studies ( Campdelacreu, 2014 ; Durazzo et al , 2014 ; Kvistad et al , 2016 ; Moss et al , 2017 ; Marck et al , 2020 ; Wang et al , 2019 ). Also, results from the lab and human research have supported the risk of long-term alcohol use in increasing the risk of epilepsy ( Leach et al , 2012 ; Welch and Derry, 2014 ; Fu et al , 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…It is also suggested that nutritional interventions may provide a better outcome for patients diagnosed with dementia ( Chen et al , 2019 ). Furthermore, the evidence for the direct and possible indirect association between tobacco and Alzheimer’s disease, as well as tobacco and multiple sclerosis, is presented in previous studies ( Campdelacreu, 2014 ; Durazzo et al , 2014 ; Kvistad et al , 2016 ; Moss et al , 2017 ; Marck et al , 2020 ; Wang et al , 2019 ). Also, results from the lab and human research have supported the risk of long-term alcohol use in increasing the risk of epilepsy ( Leach et al , 2012 ; Welch and Derry, 2014 ; Fu et al , 2016 ).…”
Section: Discussionmentioning
confidence: 97%
“…The second factor that contributes to the MS risk in our model was smoking, known as one of the most established environmental risk factors related to MS, not only in its susceptibility but also in its clinical severity [ 13 ]. Because the patients included in this study were matched by age with the controls and they had relatively short disease duration, we believe that there was no temporal difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, even by passive exposure, has recently been clearly associated with a increased risk of MS [ 13 ]. A dose-dependent response has been found both in smoking duration and in the number of cigarettes smoked, independently contributing to the increased risk.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as vitamin D deficiency, Epstein-Barr virus (EBV) infection, and cigarette smoking have been confirmed to be associated with MS; however, the mechanisms by which such variants influence disease pathophysiology are still unclear. 1-21 Several theories have been previously proposed; herein, the author proposes a new theory linked to microRNA (miRNA) biogenesis. In this review, the author explores the influence of environmental variants on the miRNA network that could affect MS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%